Activism and Dissent under State Socialism: Coalitions and Campaigns in the 1970s and 1980s. Issue 3 (1st December 2021) - Laqua, Daniel; Alston, Charlotte
Abstract : This article introduces a special Labour History Review issue on the subject of Challenges to State Socialism in Central and Eastern Europe: Activists, Movements and Alliances in the 1970s and 1980s . Our piece highlights different stimuli for dissent and opposition in the Eastern bloc, drawing attention to three strands that helped to inform political activism. First, it discusses the way in which various forms of dissident Marxism informed critiques of 'actually existing socialism' and helped activists to envision alternative ways of organizing society and state. Second, it emphasizes intersections between different actors and motivations, including links between the labour movement and forms of activism that have sometimes been categorized as 'new social movements'. Third, it notes the relevance of transnational inspirations and alliances, with a particular consideration of those that cut across the two power blocs. As a whole, the essay establishes the broader context for the case studies of activism and dissent that feature in this special journal issue.